Identification of Potential COVID-19 Targets and Pathways Derivate from Various Phenolic Compounds from Chives (Allium schoenoprasum) by Using Network Pharmacology Approach - Iksen; Buana, Bayu Cakra (MPI (Media Pharmaceutica Indonesiana), 2022)
With the uncertainty of COVID-19 disease around the world, the discovery and development of novel treatments for COVID-19 becoming an emerging trend. Network pharmacology has been used for determining the potential targets from several diseases. This research mainly focused on the potential of Allium schoenoprasum against COVID-19 based on a network pharmacology approach. The methods consist of target identification of the compounds, target identification related to COVID-19 disease, compound-target interaction network, protein-protein interaction network and gene ontology and pathway enrichment analysis. Fifthy three main targets obtained from the compound-COVID-19 were identified as main targets from the compounds with MMP9, MPO, TLR4, MMP2, CCNB1, AURKB, PLK1, TOP2A, ALOX5, and CD38 becoming the top 10 core targets. Phenolic compounds in Allium schoenoprasum may act as anti-COVID-19 through several inflammatory and immune response pathways. Based on these results, it seems that phenolic compounds in Allium schoenoprasum might act as anti-COVID-19 via network pharmacology approaches.